Positive electrode material suitable for dry-method electrode and preparation method of positive electrode material
By adjusting the synthesis conditions, the particle structure of the positive electrode material is formed into a core-shell structure of the inner and outer layer, solving the problem of easy breakage of the positive electrode particles during the dry electrode preparation process, achieving high mechanical strength and cyclic stability, and improving the overall performance of the electrode.
Patent Information
- Application Number
- CN202411867330.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-05-02
AI Technical Summary
During the preparation process of dry electrode, the particles of the positive electrode material are prone to breakage, resulting in an increase in fine powder, affecting the consistency and performance of the electrode, and traditional modification methods cannot effectively solve this problem.
By regulating the synthesis conditions, the particle structure of the positive electrode material is controlled to be agglomerated by two types of particles of different particle sizes and sizes into two core-shell structures inside and outside, improving the stability of the particle structure and the support force of the grain boundaries.
The high mechanical strength and cyclic stability of the cathode material are achieved, the particle crushing rate is reduced, and the consistency and electrochemical performance of the electrode are improved.
Smart Images

Figure CN119920870A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrode technology, and in particular to a positive electrode material suitable for a dry-process electrode and a preparation method thereof. Background Art
[0002] As the global demand for renewable energy storage grows, lithium-ion batteries have attracted widespread attention as important energy storage devices. As an emerging lithium-ion battery manufacturing technology, dry electrode technology has gradually gained attention due to its significant cost-effectiveness and environmental friendliness. However, there are some technical difficulties in the preparation of dry electrodes, especially in the fiberization process, which limits its wider application.
[0003] In the preparation process of dry electrodes, positive electrode materials (such as lithium cobalt oxide, lithium nickel manganese cobalt oxide, etc.) are usually mixed with conductive agents and adhesives, and formed into a composite material with a certain fiber structure through high-speed stirring. This fiber structure helps to improve the conductivity and mechanical strength of the electrode, but during the high-speed stirring process, the positive electrode material particles are easily subjected to strong mechanical stress, resulting in particle breakage. This process not only increases the fine powder content in the material, but may also cause agglomeration during the slurry processing, affecting the consistency and performance of the electrode.
[0004] In addition, the increase of fine powder will also lead to a series of adverse consequences, such as the generation of gas inside the battery, the decline of cycle performance, etc. The presence of fine powder increases the contact area between the electrode and the electrolyte, promotes the occurrence of side reactions, and thus affects the safety and service life of the battery.
[0005] In order to solve the above problems, the main modification methods currently adopted include doping and coating technology. Doping refers to the introduction of a small amount of other elements into the positive electrode material to improve the electrochemical performance and structural stability of the material; while coating refers to the formation of a protective film on the surface of the positive electrode material to reduce the direct contact between the material and the electrolyte and inhibit the occurrence of side reactions.
[0006] However, these traditional modification methods are still insufficient in solving the key problems that arise during the preparation of dry electrodes. For example, although doping can improve the electronic conductivity and ion diffusion rate of the material, it has limited effect on improving the mechanical strength of the secondary particles. Similarly, although coating technology can effectively reduce the side reactions between the material and the electrolyte, it cannot fundamentally solve the problem of easy breakage of particles during the cycle. Therefore, finding new methods to improve the mechanical strength and cycle stability of dry electrode materials has become the focus of current research. Summary of the invention
[0007] In order to overcome the defects of the above-mentioned prior art, the present invention provides a positive electrode material suitable for dry-process electrodes and a preparation method thereof, by adjusting the synthesis conditions to control the particle structure to be a positive electrode material in which two types of particles of different particle sizes are agglomerated into an inner and outer two-layer core-shell structure, thereby improving the stability of the particle structure and the supporting force of the grain boundary, and obtaining a positive electrode material with excellent particle size change rate, grain gap, particle strength, and capacity retention rate.
[0008] The present invention provides a positive electrode material suitable for a dry electrode, wherein the composition of the positive electrode material is shown in Formula I:
[0009] Li a Ni x Co y Mn 1-x-y O2(I)
[0010] In formula I, 0.90≤a≤1.10, 0≤x≤1, 0≤y≤1;
[0011] The positive electrode material is spherical, and consists of an inner core layer and an outer shell layer, wherein the inner core layer consists of core layer particles with a particle size of 350-550nm, and the outer shell layer consists of shell layer particles with a particle size of 200-400nm, and the particle size ratio of the core layer particles to the shell layer particles is 10:9-2:1.
[0012] Compared with the prior art, the positive electrode material provided by the present invention has two types of particles of different particle sizes in the inner and outer layers, which are closely distributed in a spherical shape. This stable self-supporting pore structure is conducive to ion diffusion, and at the same time effectively improves the particle strength of the positive electrode material, solves the problem of easy breakage of particles during the current dry mixing process, and effectively improves the comprehensive performance of the dry positive electrode material such as circulation and gas production. The preparation method is simple and convenient for commercial use. In addition, the present invention adopts an inner and outer two-layer structure of the above-mentioned particle size, and through the reasonable matching of the core layer and the shell layer particles, the material has good electronic conductivity and ion diffusion rate during the charging and discharging process, further improving the overall electrochemical performance of the battery; at the same time, the present invention adopts the particle size ratio in the above range, so that the material is not easy to produce fine powder during the mixing process, thereby avoiding the agglomeration problem in the slurry processing and improving the consistency and performance of the electrode.
[0013] In some other embodiments, the ratio of the radius of the inner core layer to the thickness of the outer shell layer is (0.2-0.8):1.
[0014] Compared with the prior art, the present invention adopts the above-mentioned thickness ratio, the main functions of which are: (1) enhancing the supporting function of the inner core layer: the radius of the inner core layer is small, which can provide strong mechanical support to prevent the material particles from breaking during high-speed stirring; (2) enhancing the protective function of the outer shell layer: the thickness of the outer shell layer is large, and a protective layer can be formed outside the inner core layer and fill the particle gaps of the inner core layer, further enhancing the overall mechanical strength of the material and reducing the mechanical damage of the material during dry stirring and preparation; (3) reducing the generation of fine powder: the particle size ratio and thickness ratio of the inner core layer and the outer shell layer are reasonably designed, which can effectively control the particle size distribution of the material and reduce the generation of fine powder.
[0015] In some other embodiments, the intergranular gap of the positive electrode material is 10-40 nm, and the range of intergranular gaps in the positive electrode material is less than or equal to 5 nm.
[0016] Compared with the prior art, the present invention adopts the above-mentioned grain gap, the main functions of which are: (1) improving electronic conductivity: smaller grain gaps (10-40nm) help to form a continuous electronic conduction path, reduce the resistance to electron transmission, and improve the overall electronic conductivity of the material; (2) optimizing lithium ion diffusion: appropriate grain gaps can provide more diffusion channels for lithium ions, reduce the transmission resistance of lithium ions inside the material, and increase the diffusion rate of lithium ions; (3) enhancing structural stability: smaller grain gaps can improve the mechanical strength of the material, reduce physical damage during high-speed stirring and charging and discharging, and improve the structural stability of the material.
[0017] In some other embodiments, the ratio of the particle size of the positive electrode material to the particle size of the core layer particles is 100:
[0018] (3-6), the particle size ratio of the positive electrode material to the shell particle size is 100:(2-5), and the particle size of the positive electrode material is 5-20 μm.
[0019] Compared with the prior art, the present invention further defines the particle size range of the positive electrode material, the particle size ratio of the positive electrode material to the core layer particles, and the particle size ratio of the positive electrode material to the shell layer particles. The main functions are: (1) Improving the consistency and uniformity of the electrode: By rationally designing the particle size ratio of the positive electrode material to the core layer particles and the shell layer particles, it is possible to ensure that the material is evenly distributed during the mixing process, reduce agglomeration, and improve the consistency and uniformity of the electrode. (2) Optimizing electrochemical performance: The rational design of the particle size ratio of the positive electrode material to the core layer particles and the shell layer particles helps to form a continuous electronic conductive network, improve the electronic conductivity of the material, and thus improve the charge and discharge efficiency of the battery; the appropriate particle size ratio can provide more diffusion paths for lithium ions, reduce the transmission resistance of lithium ions inside the material, increase the diffusion rate of lithium ions, and optimize the rate performance of the battery.
[0020] In some other embodiments, the breaking pressure of the positive electrode material is 150-200 MPa, and the particle size change rate of the positive electrode material particles is less than 4% before and after the dry stirring process.
[0021] The second object of the present invention is to provide a method for preparing a positive electrode material, the preparation method specifically comprising the following steps:
[0022] S1. Perform a precursor synthesis reaction on nickel sulfate, cobalt sulfate, manganese sulfate, sodium hydroxide solution and ammonia water according to a molar ratio. When the particle size of the obtained product particles is greater than or equal to 3-4 μm, adjust the reaction parameters to perform a growth reaction until the particle size of the obtained product particles is greater than or equal to 10 μm, and then terminate the reaction;
[0023] S2, subjecting the product obtained in step S1 to aging, solid-liquid separation, washing, drying and sieving in sequence to obtain a precursor material;
[0024] S3. Add the precursor material obtained in step S2 into a high-speed mixer, add lithium hydroxide monohydrate at a lithiation coefficient molar ratio of 1:1, stir and mix, put into a sagger, place in an oxygen atmosphere for roasting, cool to room temperature after the roasting, and sequentially wash, centrifuge, dry, and grind to obtain a positive electrode material.
[0025] Compared with the prior art, the present invention adopts the above-mentioned preparation method to prepare positive electrode materials with high mechanical strength and stable particle size, and the prepared positive electrode materials show excellent mechanical stability, reduced particle size variation, improved electrode consistency and uniformity, optimized electrochemical performance, enhanced cycle performance and reduced side reactions during the dry electrode preparation process.
[0026] In some other embodiments, in step S1, the parameters of the precursor synthesis reaction are as follows: temperature is 60-80°C, pH is 11-13, and ammonia value is 3-5 g / L.
[0027] Compared with the prior art, the present invention adopts the above parameters to carry out the precursor synthesis reaction, and the main functions are: (1) when the temperature is controlled to be 60-80°C, a suitable reaction environment can be provided to promote the uniform growth of the precursor, and this temperature range can ensure the activity of the reaction without being too high to cause side reactions; (2) when the pH value is 11-13, the precipitation process of the precursor can be effectively controlled to ensure that the generated particles are uniform and have high purity. Too high a pH value will cause the precipitation to be too fast and the particle size is uneven. Too low a pH value will affect the formation of the precursor; (3) when the ammonia value is 3-5g / L, a sufficient alkaline environment can be provided to promote the precipitation of metal ions, while avoiding side reactions caused by excessive ammonia water, which is helpful to form uniform precursor particles. Through the precise control of the above parameters, the particle size of the precursor particles can be effectively controlled so that it continues to grow above 4μm until it reaches 10μm.
[0028] In some other embodiments, in step S1, the parameters of the growth reaction are as follows: temperature of 50-60°C, pH of 10-11.5, and ammonia value of 3-5 g / L.
[0029] Compared with the prior art, the present invention adopts the above parameters to carry out the subsequent growth reaction, and the main functions are: (1) When the temperature is 50-60°C, a relatively mild reaction environment can be provided, which is conducive to the uniform growth of the precursor particles. This temperature range can ensure the progress of the reaction without causing an excessively fast reaction rate, thereby avoiding uneven growth of the particles; (2) When the pH value is 10-11.5, a moderate alkaline environment can be maintained, which is conducive to the slow and uniform growth of the precursor particles. Too high a pH value will cause the particles to grow rapidly and may form larger agglomerates; too low a pH value will affect the formation and stability of the particles; (3) When the ammonia value is 3-5g / L, a sufficient alkaline environment can be provided to promote the precipitation of metal ions while avoiding side reactions caused by excessive ammonia water. The appropriate amount of ammonia value helps to form uniform precursor particles. Therefore, suitable temperature, pH value and ammonia value can significantly improve the uniform growth of precursor particles, improve the crystallinity and purity of the precursor, reduce side reactions and impurities, and improve the stability of the precursor.
[0030] Combined with step S1, the present invention first rapidly nucleates at a high pH value and a relatively high temperature to promote the spherical growth of the crystal nucleus in the radial direction, and then injects the nucleated particles into an environment with a low pH value and a relatively low temperature to promote their secondary growth on the particle surface, thereby obtaining two types of spherical core-shell structured positive electrode materials with different particle sizes, with a larger inner particle size and a smaller outer particle size.
[0031] In some other embodiments, in step S2, the aging time is 6-20 hours.
[0032] Compared with the prior art, the present invention sets the aging time to 6-20 hours, which can ensure that the precursor particles are fully homogenized during the aging process. During this period, the composition and structure inside the particles will gradually become consistent, reducing the performance differences caused by local unevenness. At the same time, the appropriate aging time helps to stabilize the structure of the precursor particles, reduce decomposition and deterioration in the subsequent processing process, and during the aging process, the stress inside the particles will gradually release, improving the mechanical strength and stability of the particles.
[0033] In some other embodiments, in step S3, the stirring and mixing parameters are as follows: rotation speed is 200-600 rpm, and time is 50-250 min.
[0034] Compared with the prior art, the present invention adopts parameters for stirring and mixing. Appropriate rotation speed and mixing time can ensure uniform mixing of materials and avoid local over-mixing or insufficient mixing. Uniform mixing helps to form a stable crystal structure and improve the mechanical strength of the material.
[0035] In some other embodiments, in step S3, the parameters of the calcination treatment are as follows: temperature is 650-950° C., and time is 6-25 h.
[0036] Compared with the prior art, the present invention adopts the above parameters for calcination treatment, wherein when the temperature is 650-950°C, sufficient thermal energy can be provided to promote the crystallization process of the precursor material. Within this temperature range, the metal ions in the material can be rearranged to form a stable crystal structure; and the calcination time is 6-25 hours, which can ensure that the material fully reacts at high temperature to form a uniform crystal structure. This period of time is long enough to ensure that the crystallization process of the material is completely carried out, but not too long to avoid excessive sintering and structural damage of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A schematic diagram of the structure of the ternary positive electrode material prepared in Example 1;
[0038] Figure 2 This is a SEM image of the ternary cathode material prepared in Example 1;
[0039] Figure 3 TEM image of the secondary spherical particles of the ternary cathode material prepared in Example 1 and the corresponding grain gap;
[0040] Figure 4 This is a cross-sectional SEM image of the ternary cathode material prepared in Example 1;
[0041] Figure 5 This is a SEM comparison of the ternary cathode material prepared in Example 1 before and after dry stirring;
[0042] Figure 6 This is a cross-sectional SEM image of the ternary cathode material prepared in Comparative Example 4;
[0043] Figure 7 This is a SEM comparison picture of the ternary positive electrode material prepared in Comparative Example 4 before and after dry stirring. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0046] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0047] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0048] It is worth mentioning that in the detection method adopted in the embodiment of the present invention:
[0049] Particle size testing method: SEM-based electron backscatter diffraction analysis (EBSD) technology uses crystallographic information to construct an orientation map of each grain on the sample surface, automatically calibrate the grain boundaries, and count the grain size.
[0050] Testing method for grain spacing: Energy dispersive X-ray spectroscopy (EDS) analysis is performed using a transmission electron microscope (TEM) to measure the grain spacing between grain boundaries.
[0051] The particle strength detection method is as follows: using Shimadzu DUH-211S equipment, under a 500x microscope, take a single dispersed ternary material secondary particle, apply pressure with a 50μm flat pressure head, record the corresponding pressure and pressure, and obtain the pressure corresponding to the particle crushing.
[0052] Embodiment 1:
[0053] This embodiment provides a method for preparing a ternary positive electrode material suitable for a dry electrode, and the specific steps are as follows:
[0054] Nickel sulfuric acid, cobalt sulfate, manganese sulfate solution (molar ratio of Ni: Co: Mn = 8: 1: 1, the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution at a reaction temperature of 70 ° C, pH = 12, ammonia value of 3.5 g / L conditions for precursor synthesis reaction, when the precursor particle size reaches 3 μm, the reaction temperature is adjusted to 55 ° C, pH = 10.5, ammonia value of 3.0 g / L for growth reaction, when the particle size grows to 10 μm after the reaction is terminated, the reaction product is aged for 12 hours, and then solid-liquid separation, washing, drying, sieving to obtain the precursor material Ni 0.8 Co 0.1 Mn 0.1 (OH)2. Add 1 kg of the precursor Ni prepared by the above method into the high-speed mixer. 0.8 Co 0.1 Mn 0.1 (OH)2, lithium hydroxide monohydrate was added at a molar ratio of 1:1 for the lithiation coefficient, the mixture was stirred at 300 rpm for 120 min, and then put into a sagger, and calcined at 800 ° C for 12 h in an oxygen atmosphere (oxygen concentration ≥ 80%). After cooling to room temperature, it was washed with water, centrifuged, dried, and ground to obtain LiNi with excellent particle strength. 0.8 Co 0.1 Mn 0.1 O2 spherical particles can be used to produce dry-process batteries with good cycle retention rate and excellent gas production performance.
[0055] Figure 1 It is a schematic diagram of the structure of the ternary positive electrode material prepared in this embodiment. The particles are divided into two types of structures as a whole: the inner core layer has a grain size of 400nm, and the outer shell layer has a grain size of 240-260nm. The outer shell layer can fill the gaps in the inner core layer. The whole is densely packed and distributed along the radial direction from the inside to the outside. The radius of the inner core layer is 1.35μm, and the thickness of the outer shell layer is 3.65μm. The whole is loose and porous, with a small porosity and close contact between grain boundaries.
[0056] Figure 2 is a SEM image of the ternary cathode material prepared in this embodiment, Figure 3 This is a TEM image of the particles of the ternary positive electrode material prepared in this embodiment. It is measured that the grain gap of the prepared positive electrode material particles is in the range of 25-26nm.
[0057] The ternary cathode material prepared in this example was ground in a mortar for 10 minutes and then characterized by the material profile. Figure 4 This is a cross-sectional SEM image of the ternary cathode material prepared in this embodiment. Figure 4It can be seen that the prepared positive electrode material has a stable self-supporting pore structure of core layer and shell layer.
[0058] The prepared cathode material was dry-stirred for 3 min and then characterized. Figure 5 The SEM images of the ternary positive electrode material before and after dry stirring are shown in Tables 1 and 2. Detailed particle size parameters and test results are shown in Tables 1 and 2. According to Table 2, the change rate of the particle size of the prepared ternary positive electrode material after dry stirring is 2.7%, indicating that the two types of structured positive electrode materials synthesized can effectively improve the particle strength.
[0059] Embodiment 2:
[0060] This embodiment provides a ternary positive electrode material suitable for a dry electrode, and its preparation process is different from that of Example 1 only in that, during the preparation process of this embodiment, the reaction conditions of the first step synthesis reaction of the precursor are adjusted to a reaction temperature of 65°C, pH=11.5, and an ammonia value of 3.4 g / L.
[0061] After testing, the core layer grain size of the ternary positive electrode material synthesized in this embodiment is 340nm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0062] It can be seen from the combination of Example 1 and Example 2 that within the range of particle size parameters and particle size ratio of the synthesis reaction of the present invention, positive electrode materials with good particle strength can be obtained.
[0063] Embodiment 3:
[0064] This embodiment provides a method for preparing a ternary positive electrode material suitable for a dry electrode. The only difference from Example 1 is that the synthesis reaction conditions of the second step of the precursor in this embodiment are adjusted to a reaction temperature of 60°C, pH=11.1, and an ammonia value of 3.2 g / L. The rest is the same as Example 1 and will not be repeated here.
[0065] After testing, the outer shell layer of the ternary positive electrode material synthesized in this embodiment has a grain size of 300-320 nm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0066] It can be seen from the combination of Example 1 and Example 3 that within the range of particle size parameters and particle size ratio of the synthesis reaction of the present invention, positive electrode materials with good particle strength can be obtained.
[0067] Embodiment 4:
[0068] This embodiment provides a method for preparing a ternary positive electrode material suitable for a dry electrode. The only difference from Example 1 is that the synthesis reaction conditions of the second step of the precursor in this embodiment are adjusted to a reaction temperature of 50°C, pH=10.1, and an ammonia value of 2.9 g / L. The rest is the same as Example 1 and will not be repeated here.
[0069] After testing, the outer shell layer grain size of the ternary positive electrode material synthesized in this embodiment is 210-230nm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0070] It can be seen from the combination of Example 1 and Example 4 that within the range of particle size parameters and particle size ratio of the synthesis reaction of the present invention, positive electrode materials with good particle strength can be obtained.
[0071] Embodiment 5:
[0072] This embodiment provides a ternary positive electrode material suitable for dry-process electrodes. The preparation process thereof is different from that of Embodiment 1 only in that, when the precursor particle size reaches 4.5 μm, the reaction temperature is adjusted to 55°C, pH=10.5, and the ammonia value is 3.0 g / L for the growth reaction until the reaction ends when the particle size grows to 10 μm. The rest is the same as Embodiment 1 and will not be repeated here.
[0073] After testing, the radius of the inner core layer of the ternary positive electrode material synthesized in this embodiment is 2.05 μm, and the thickness of the outer shell layer is 2.95 μm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0074] It can be seen from the combination of Example 1 and Example 5 that within the particle size thickness of the core layer and the shell layer of the synthesis reaction of the present invention, positive electrode materials with good particle strength can be synthesized.
[0075] Embodiment 6:
[0076] This embodiment provides a ternary positive electrode material suitable for dry electrodes. The preparation process thereof is different from that of Example 1 only in that, when the precursor particle size reaches 2.5 μm, the reaction temperature is adjusted to 55°C, pH=10.5, and the ammonia value is 3.0 g / L for the growth reaction until the reaction ends when the particle size grows to 10 μm. The rest is the same as Example 1 and will not be repeated here.
[0077] After testing, the radius of the inner core layer of the ternary positive electrode material synthesized in this embodiment is 1.05 μm, and the thickness of the outer shell layer is 3.95 μm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0078] It can be seen from the combination of Example 1 and Example 6 that within the particle size thickness of the core layer and the shell layer of the synthesis reaction of the present invention, positive electrode materials with good particle strength can be synthesized.
[0079] Embodiment 7:
[0080] This embodiment provides a ternary positive electrode material suitable for dry electrodes. The preparation process thereof is different from that of Example 1 only in that, when the precursor particle size reaches 4.5 μm, the reaction temperature is adjusted to 55°C, pH=10.5, and the ammonia value is 3.0 g / L for the growth reaction until the reaction ends when the particle size grows to 12 μm. The rest is the same as Example 1 and will not be repeated here.
[0081] After testing, the radius of the inner core layer of the ternary positive electrode material synthesized in this embodiment is 2.05 μm, the thickness of the outer shell layer is 5.45 μm; the particle size of the synthesized positive electrode material is 12 μm; the particle size ratio of the synthesized positive electrode material to the core layer particles is 100:3.33, and the particle size ratio of the synthesized positive electrode material to the shell layer particles is 100:2.08. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0082] It can be seen from Example 1 and Example 7 that within the range of the positive electrode material particle size of the synthesis reaction of the present invention and the corresponding positive electrode material particle size to the particle size ratio of the core layer and the shell layer particles, positive electrode materials with good particle strength can be synthesized.
[0083] Embodiment 8:
[0084] This embodiment provides a ternary positive electrode material suitable for dry electrodes. The preparation process thereof is different from that of Embodiment 1 only in that, when the precursor particle size reaches 2.5 μm, the reaction temperature is adjusted to 55°C, pH=10.5, and the ammonia value is 3.0 g / L for the growth reaction until the reaction ends when the particle size grows to 8 μm. The rest is the same as that of Embodiment 1 and will not be repeated here.
[0085] After testing, the radius of the inner core layer of the ternary positive electrode material synthesized in this embodiment is 1.05 μm, the thickness of the outer shell layer is 2.95 μm; the particle size of the synthesized positive electrode material is 8 μm; the particle size ratio of the synthesized positive electrode material to the core layer particles is 100:5, and the particle size ratio of the synthesized positive electrode material to the shell layer particles is 100:3.13. Detailed particle size parameters and test result data are shown in Tables 1 and 2.
[0086] It can be seen from Example 1 and Example 8 that within the range of the positive electrode material particle size of the synthesis reaction of the present invention and the corresponding positive electrode material particle size to the particle size ratio of the core layer and the shell layer particles, positive electrode materials with good particle strength can be synthesized.
[0087] Embodiment 9:
[0088] This embodiment provides a ternary positive electrode material suitable for dry electrode. The preparation process thereof is different from that of embodiment 1 only in that nickel sulfate, cobalt sulfate and manganese sulfate salt solution are mixed in a molar ratio of 90:6:4 in this embodiment. The rest is the same as embodiment 1 and will not be described again. LiNi is obtained after synthesis in this embodiment. 0.90 Co 0.06 Mn 0.04 O2 positive electrode material.
[0089] It can be seen from the combination of Example 1 and Example 9 that the positive electrode material with good particle strength can be obtained by adopting the element composition range of this embodiment.
[0090] Embodiment 10:
[0091] This embodiment provides a ternary positive electrode material suitable for dry electrode, and the preparation process thereof is different from that of embodiment 1 only in that, in the preparation process of this embodiment, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor, LiOH, Al2O3, ZrO2, and TiO2 are mixed in a molar ratio of 1:0.90:0.15:0.1:0.05 in a ball mill, first mixed at 300 rpm for 1 hour, then mixed at 600 rpm for 7 hours. After mixing, the mixture is placed in a sagger and calcined at 800°C for 12 hours in an oxygen atmosphere (oxygen concentration ≥ 80%). After cooling to room temperature, the spherical secondary particles of doped ternary positive electrode material are obtained after washing, centrifugation, drying, and grinding.
[0092] It can be seen from the combination of Example 1 and Example 10 that on the basis of the precursor material synthesized by the present invention, by doping and coating other elements, a positive electrode material with good particle strength can still be obtained.
[0093] Comparative Example 1:
[0094] The present comparative example provides a ternary positive electrode material suitable for a dry electrode, and the preparation process thereof is as follows: nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solution (molar ratio of Ni: Co: Mn = 8: 1: 1, and the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution are subjected to a precursor synthesis reaction under the conditions of adjusting the reaction temperature to 55°C, pH = 10.5, and an ammonia value of 3.0 g / L. When the precursor particle size reaches 3 μm, the growth reaction is carried out under the conditions of adjusting the reaction temperature to 70°C, pH = 12, and an ammonia value of 3.5 g / L. When the particle size grows to 10 μm, the reaction is terminated, and the reaction product is aged for 12 hours, and then solid-liquid separation, washing, drying, and sieving are performed to obtain a precursor material Ni 0.8 Co 0.1 Mn 0.1(OH)2. Add 1 kg of the precursor Ni prepared by the above method into the high-speed mixer. 0.8 Co 0.1 Mn 0.1 (OH)2, lithium hydroxide monohydrate was added at a molar ratio of 1:1 according to the lithiation coefficient, the mixture was stirred at 300 rpm for 120 min, and then put into a sagger, and calcined at 800 ° C for 12 h in an oxygen atmosphere (oxygen concentration ≥ 80%), and then cooled to room temperature, washed, centrifuged, dried, and ground to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 spherical particles.
[0095] After testing, the ternary cathode material synthesized in this comparative example is a secondary particle composed of an inner core layer with a grain size of 250nm and an outer shell layer with a grain size of 400nm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0096] Combining Example 1 and Comparative Example 1, it can be seen that the synthesized secondary particles with small inner grains and large outer grains have larger outer grain gaps, which makes it more likely for particles to break during the dry mixing process. In addition, the smaller inner particles lead to increased resistance to lithium ion transmission within the material, reduced capacity, and a certain degree of lithium loss.
[0097] Comparative Example 2:
[0098] The present comparative example provides a ternary positive electrode material suitable for a dry electrode, and the preparation process thereof is as follows: nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solution (molar ratio of Ni: Co: Mn = 8: 1: 1, and the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution are subjected to a precursor synthesis reaction under the conditions of adjusting the reaction temperature to 70°C, pH = 12, and an ammonia value of 3.5 g / L. When the precursor particle size reaches 6 μm, the reaction temperature is adjusted to 55°C, pH = 10.5, and an ammonia value of 3.0 g / L for growth reaction. When the particle size grows to 10 μm, the reaction is terminated, and the reaction product is aged for 12 hours, and then solid-liquid separation, washing, drying, and sieving are performed to obtain a precursor material Ni 0.8 Co 0.1 Mn 0.1 (OH)2. Add 1 kg of the precursor Ni prepared by the above method into the high-speed mixer. 0.8 Co 0.1 Mn 0.1(OH)2, lithium hydroxide monohydrate was added at a molar ratio of 1:1 according to the lithiation coefficient, the mixture was stirred at 300 rpm for 120 min, and then put into a sagger, and calcined at 800 ° C for 12 h in an oxygen atmosphere (oxygen concentration ≥ 80%), and then cooled to room temperature, washed, centrifuged, dried, and ground to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 spherical particles.
[0099] After testing, the core-shell structure ternary positive electrode material synthesized in this comparative example has a core layer radius of 2.85 μm and a shell layer thickness of 2.15 μm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0100] Combining Example 1 and Comparative Example 2, it can be seen that the radius of the synthesized inner core layer is larger and the thickness of the outer shell layer is smaller. Since the inner layer particle size is larger and the grain gap is larger, the overall grain gap of the positive electrode material is larger, the protective effect of the outer core layer is reduced, and the particle strength is reduced. The positive electrode roasting process and the dry electrode preparation process lead to an increase in fine powder and a decrease in electrical performance.
[0101] Comparative Example 3
[0102] The present comparative example provides a ternary positive electrode material suitable for a dry electrode, and the preparation process thereof is as follows: nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solution (molar ratio of Ni: Co: Mn = 8: 1: 1, and the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution are subjected to a precursor synthesis reaction under the conditions of adjusting the reaction temperature to 55°C, pH = 10.5, and an ammonia value of 3.0 g / L. When the precursor particle size reaches 6 μm, the growth reaction is carried out under the conditions of adjusting the reaction temperature to 70°C, pH = 12, and an ammonia value of 3.5 g / L. When the particle size grows to 10 μm, the reaction is terminated, and the reaction product is aged for 12 hours, and then solid-liquid separation, washing, drying, and sieving are performed to obtain a precursor material Ni 0.8 Co 0.1 Mn 0.1 (OH)2. Add 1 kg of the precursor Ni prepared by the above method into the high-speed mixer. 0.8 Co 0.1 Mn 0.1 (OH)2, lithium hydroxide monohydrate was added at a molar ratio of 1:1 according to the lithiation coefficient, the mixture was stirred at 300 rpm for 120 min, and then put into a sagger, and calcined at 800 ° C for 12 h in an oxygen atmosphere (oxygen concentration ≥ 80%), and then cooled to room temperature, washed, centrifuged, dried, and ground to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 spherical particles.
[0103] After testing, the ternary cathode material synthesized in this comparative example is composed of secondary particles with an inner core layer grain size of 250nm and an outer shell layer grain size of 400nm, an inner core layer radius of 2.65μm, and an outer shell layer thickness of 2.35μm. Detailed particle size parameters and test results are shown in Tables 1 and 2.
[0104] Combining Example 1 and Comparative Example 3, it can be seen that the synthesized core-shell structured secondary particles have a smaller inner core layer particle size and a larger inner core layer radius, which seriously reduces the diffusion of lithium ions inside and enhances its diffusion resistance; the outer shell layer particle size is larger, the grain gap is larger, and side reactions are prone to occur on the surface of the secondary particles, resulting in increased gas production and poor cycle performance.
[0105] Comparative Example 4:
[0106] This comparative example provides a ternary positive electrode material suitable for a dry electrode, and its preparation process is different from that of Example 1 only in that nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solutions (molar ratio of Ni: Co: Mn = 8: 1: 1, the three solutions are mixed at a concentration of 1.5 mol / L) with 4 mol / L sodium hydroxide solution and ammonia solution at a reaction temperature of 60°C, pH = 11.5, and an ammonia value of 3.5 g / L. The reaction ends when the particle size grows to 10 μm.
[0107] The synthesized ternary positive electrode material is a disorderly arrangement of particles with a grain size of 350-380nm.
[0108] The ternary cathode material prepared in this comparative example was ground in a mortar for 10 minutes and then characterized by the material profile. Figure 6 This is a cross-sectional SEM image of the ternary cathode material prepared in Comparative Example 4. Figure 7 These are the SEM images of the prepared ternary positive electrode material before and after dry stirring.
[0109] Combining Example 1 and Comparative Example 4, it can be concluded that the stable self-supporting pore structure is conducive to Li + It can effectively improve the particle strength of the positive electrode material by embedding and unembedding. If only a single synthesis of disordered positive electrode materials is used, good self-supporting grain boundaries cannot be formed, which reduces the stability of the particle structure and leads to an increase in particle breakage and fine powder during grinding and dry mixing, resulting in poor subsequent gas production and cycle performance.
[0110] Comparative Example 5:
[0111] The present comparative example provides a ternary positive electrode material suitable for a dry electrode, and the preparation process is as follows: nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solution (molar ratio of Ni: Co: Mn = 8: 1: 1, the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution under the conditions of reaction temperature of 60 ° C, pH = 11.5, and ammonia value of 3.5 g / L. When the particle size grows to 10 μm, the reaction is terminated to obtain porous and loose secondary particles, and Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor, LiOH, Al2O3, ZrO2, and TiO2 are mixed in a molar ratio of 1:0.90:0.15:0.1:0.05 in a ball mill, first mixed at 300 rpm for 1 hour, then mixed at 600 rpm for 7 hours. After mixing, the mixture is placed in a sagger and calcined at 800°C for 12 hours in an oxygen atmosphere (oxygen concentration ≥ 80%). After cooling to room temperature, the spherical secondary particles of doped ternary positive electrode material are obtained after washing, centrifugation, drying, and grinding.
[0112] It can be seen from Example 1 and Comparative Example 5 that even if element doping is performed on the basis of a single synthesis of disordered cathode materials, although the problem of particle breakage can be improved to a certain extent, the improvement effect is not significant, which further illustrates the necessity and excellence of the two reactions of the present invention.
[0113] Comparative Example 6:
[0114] The present comparative example provides a ternary positive electrode material suitable for a dry electrode, and the preparation process is as follows: nickel sulfuric acid, cobalt sulfate, and manganese sulfate salt solution (molar ratio of Ni: Co: Mn = 8: 1: 1, the three solutions are mixed at a concentration of 1.5 mol / L) and 4 mol / L sodium hydroxide solution and ammonia solution under the conditions of reaction temperature of 60 ° C, pH = 11.5, and ammonia value of 3.5 g / L. When the particle size grows to 10 μm, the reaction is terminated to obtain porous and loose secondary particles, and Ni 0.8 Co 0.1 Mn 0.1(OH)2 precursor, LiOH, CeO2 are mixed in a molar ratio of 1:0.95:0.05 and mixed in a ball mill at 600rpm for 7h. After mixing, put it into a sagger in an oxygen atmosphere (oxygen concentration ≥80%), pre-sinter it at 600℃, then heat it to 750℃ for sintering for 12h, cool it to room temperature, then wash it with 1:1 water for 10 minutes, then centrifuge it at 1000rpm for 15min, then dry it in an oven at 140℃ for 5 hours, add the dried ternary material to a planetary ball mill, use zirconium oxide ball milling beads, and control the ball-to-material ratio at 1:3. Then, add 5g of H3BO3, ball mill at 300rpm for 3h, separate the ball milling beads and ball milling material, put the two ingredients into a sagger, pass into an oxygen atmosphere (oxygen concentration ≥80%), and sinter it at 350℃ for 12h. After cooling to room temperature, the spherical secondary particles of the ternary cathode material with surface doping are obtained through water washing, centrifugation, drying and grinding.
[0115] It can be seen from Example 1 and Comparative Example 6 that the surface strength is improved by introducing ion doping with a moderate radius on the basis of a single synthesis of disordered positive electrode materials. Although surface doping can improve the particle strength to a certain extent, the internal arrangement structure of the positive electrode material is unstable, resulting in grain boundary cracking during the cycle process, breakage of the positive electrode material, and deterioration of the cycle performance.
[0116] Furthermore, the inventors tested the physical properties of the positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-6, and the results are shown in Tables 1 and 2, wherein Table 1 shows the particle size parameters, particle size ratio and core-shell thickness ratio data of the ternary positive electrode materials prepared in Examples 1-10 and Comparative Examples 1-6 of the present invention; Table 2 shows the particle size parameters, grain gaps, and particle strength capacity retention rate data of the ternary positive electrode materials prepared in Examples 1-10 and Comparative Examples 1-6 of the present invention before and after the dry mixing process.
[0117] The particle size parameters of the positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-6 are summarized in Table 1:
[0118] Table 1: Summary of particle size parameters of positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-6
[0119]
[0120] The performance test results of the positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-6 are shown in Table 2:
[0121] Table 2: Performance test results of positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-6
[0122]
[0123] It can be seen from Table 1 and Table 2 that: First, the core layer particle size of the positive electrode material prepared by the present invention is between 350-550 nm, and the particle size of the shell layer particles is between 200-400 nm. At the same time, the particle size ratio of the core layer particles to the shell layer particles of the positive electrode material prepared by the embodiment of the present invention is in the range of 10:9-2:1, while in Comparative Examples 1 and 3, the particle size ratio of the core layer particles to the shell layer particles of the positive electrode material is 0.625. Combined with Table 2, it can be seen that the particle size ratio of the core layer particles to the shell layer particles is directly related to the particle strength of the prepared positive electrode material. Compared with the positive electrode material whose particle size ratio is not within the range specified by the present invention, when the particle size ratio is within the range specified by the present invention, the obtained positive electrode material has a higher particle strength, so when it is used in a battery, it also has a better capacity retention rate;
[0124] Second, the present invention further defines the thickness ratio of the core-shell layer as (0.2-0.8): 1, while the thickness ratio of the core-shell layer of the positive electrode material obtained in Comparative Example 2 is 1.33: 1, and the thickness ratio of the core-shell layer of the positive electrode material obtained in Comparative Example 3 is 1.13: 1, both of which are not within the scope of the present invention. Combined with the particle strength of Table 2, it can be seen that compared with the positive electrode material whose core-shell thickness ratio is not within the scope of the present invention, when the core-shell thickness ratio is within the scope of the present invention, the obtained positive electrode material has a higher particle strength, and can also have a better capacity retention rate when used in a battery. The reason for this is that the radius of the inner core layer is small, which can provide strong mechanical support to prevent the material particles from breaking during high-speed stirring, and the thickness of the outer shell layer is large, which can form a protective layer outside the inner core layer and fill the particle gaps of the inner core layer, further enhancing the overall mechanical strength of the material.
[0125] Third, the present invention further defines the ratio of the particle size of the positive electrode material to the particle size of the core layer particles as 100: (3-6), and the ratio of the particle size of the positive electrode material to the particle size of the shell layer particles as 100: (2-5). The particle size ratios of the core layer particles of the positive electrode materials obtained in Comparative Examples 1 and 3 are both 100: 2.4, which are not within the scope of the present invention. Combined with the particle strength of Table 2, it can be seen that compared with the positive electrode material whose particle size ratio of the positive electrode material to the core layer particles is not within the scope of the present invention, when the particle size ratio of the positive electrode material to the core layer particles is within the scope of the present invention, the obtained positive electrode material has a higher particle strength and can also have a better capacity retention rate when used in the battery. The reason for this is that by reasonably designing the particle size ratio of the positive electrode material to the core layer particles and the shell layer particles, it is possible to ensure that the material is evenly distributed during the mixing process, reduce agglomeration, and improve the consistency and uniformity of the electrode; further, it is helpful to form a continuous electronic conductive network, improve the electronic conductivity of the material, and thus improve the charge and discharge efficiency of the battery.
[0126] It can be seen from the above results that the present invention controls the particle structure by adjusting the synthesis conditions so that two types of primary particles with different particle sizes are agglomerated into secondary particles with an inner and outer core-shell structure, thereby improving the stability of the particle structure and the supporting force of the grain boundaries, and obtaining a positive electrode material with excellent particle size change rate, grain gap, particle strength, and capacity retention rate.
[0127] At the same time, the particle size change rate, grain gap, particle strength, and capacity retention rate of the positive electrode material prepared using disordered precursors after dry stirring are all poor; the use of element doping and the introduction of ion surface doping with a moderate radius have a certain effect on improving particle strength, but the resulting positive electrode material still has poor particle size change rate, grain gap, particle strength, and capacity retention rate.
[0128] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A positive electrode material suitable for a dry electrode, characterized in that: The composition of the positive electrode material is shown in Formula I: Li a Ni x Co y Mr 1-x-y O2(I) In formula I, 0.90≤a≤1.10, 0≤x≤1, 0≤y≤1; The positive electrode material is spherical, and consists of an inner core layer and an outer shell layer, wherein the inner core layer consists of core layer particles with a particle size of 350-550nm, and the outer shell layer consists of shell layer particles with a particle size of 200-400nm, and the particle size ratio of the core layer particles to the shell layer particles is 10:9-2:
1.
2. The positive electrode material according to claim 1, characterized in that The ratio of the radius of the inner core layer to the thickness of the outer shell layer is (0.2-0.8):
1.
3. The positive electrode material according to claim 1, characterized in that The grain gap of the positive electrode material is 10-40nm, and the range of the grain gap in the positive electrode material is less than or equal to 5nm. The grain gap of the core layer particles is 10-40nm, and the grain gap of the shell layer particles is 10-40nm, and the range of the grain gap is less than or equal to 5nm.
4. The positive electrode material according to claim 1, characterized in that The particle size ratio of the positive electrode material to the core layer particles is 100:(3-6), and the particle size ratio of the positive electrode material to the shell layer particles is 100: (2-5), the particle size of the positive electrode material is 5-20 μm.
5. The positive electrode material according to claim 1, characterized in that The breaking pressure of the positive electrode material is 150-200 MPa, and the particle size change rate of the positive electrode material particles is less than 4% before and after the dry stirring process.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method specifically comprises the following steps: S1. Perform a precursor synthesis reaction on nickel sulfate, cobalt sulfate, manganese sulfate, sodium hydroxide solution and ammonia water according to a molar ratio. When the particle size range of the obtained product particles is 1-5 μm, adjust the reaction parameters for secondary synthesis until the particle size range of the obtained product particles is 5-20 μm, and then terminate the reaction; S2, subjecting the product obtained in step S1 to aging, solid-liquid separation, washing, drying and sieving in sequence to obtain a precursor material; S3. Add the precursor material obtained in step S2 into a high-speed mixer, add lithium hydroxide monohydrate at a lithiation coefficient molar ratio of 1:1, stir and mix, put into a sagger, place in an oxygen atmosphere for roasting, cool to room temperature after the roasting, and sequentially wash, centrifuge, dry, and grind to obtain a positive electrode material.
7. The preparation method according to claim 6, characterized in that: In step S1, the parameters of the precursor synthesis reaction are as follows: temperature is 60-80°C, pH is 11-13, and ammonia value is 3-5 g / L.
8. The preparation method according to claim 6, characterized in that: In step S1, the parameters of the growth reaction are as follows: temperature is 50-60° C., pH is 10-11.5, and ammonia value is 3-5 g / L.
9. The preparation method according to claim 6, characterized in that: In step S2, the aging time is 6-20 hours; and / or, In step S3, the stirring and mixing parameters are as follows: the rotation speed is 200-600 rpm, and the time is 50-250 min.
10. The preparation method according to claim 6, characterized in that: In step S3, the parameters of the calcination treatment are as follows: temperature is 650-950° C., and time is 6-25 hours.